Treatment for childhood acute lymphoblastic leukemia in Taiwan: Taiwan Pediatric Oncology Group ALL‐2002 study emphasizing optimal reinduction therapy and central nervous system preventive therapy without cranial radiation. Issue 2 (3rd October 2016) - Li, Meng‐Ju; Liu, Hsi‐Che; Yen, Hsiu‐Ju; Jaing, Tang‐Her; Lin, Dong‐Tsamn; Yang, Chao‐Ping; Lin, Kai‐Hsin; Hung, Iou‐Jih; Jou, Shiann‐Tarng; Lu, Meng‐Yao; Hsiao, Chih‐Cheng; Peng, Ching‐Tien; et al.
Abstract: Background: Reinduction therapy has improved the outcomes in children with acute lymphoblastic leukemia (ALL). We sought to determine the optimal course(s) of reinduction therapy for standard‐risk (SR, or "low‐risk" in other groups) patients. Also, we evaluated outcomes using triple intrathecal therapy without cranial radiation (CrRT) for central nervous system (CNS) preventive therapy. Procedure: From 2002 to 2012, all newly diagnosed children with ALL in Taiwan were enrolled in Taiwan Pediatric Oncology Group ALL‐2002 protocol. SR patients were randomized to receive single or double reinduction courses. The patients enrolled before 2009 received CrRT, while those enrolled later did not. The Kaplan–Meier method was used to estimate survival rates and the difference between two groups was compared by the two‐sided log‐rank test. Results: In 1, 366 eligible patients, the 5‐year overall survival (OS) was 81.6 ± 1.1% (standard error) and 5‐year event‐free survival (EFS) was 74.3 ± 1.2%. In SR patients, the 5‐year OS for one and two reinduction courses was 91.6 ± 2.1% and 93.7 ± 1.8%, respectively, and the 5‐year EFS was 85.2 ± 2.7% and 89.8 ± 2.3%, respectively. There were no significant differences in survival between these two groups. Patients with MLL or BCR‐ABL1 had the worst outcomes: 5‐year EFS was 23.4 and 31.8% and 5‐year OS was 28.6 and 44.7%, respectively. There was no significant difference in CNS relapse or survival between the era with or without CrRT. Conclusions: For SR patients, one‐course reinduction was adequate. Triple intrathecal therapy alone successfully prevented CNS relapse.